Vietnam : Transition to a Market Economy - Srinivasan, Krishna; Braulke, M.; Mulder, Christian; Spitaller, Erich (Washington, D.C. : International Monetary Fund, 1996)
The paper explores the pattern of transition of the Vietnamese economy, the policies that were applied, and the reasons for the country's success. In particular, it focuses on output performance; state-owned enterprises; foreign direct investment; determinants of inflation; dollarization and problems of economic management; international integration and exchange rate policy; growth and diversification of trade, trade reform, exchange reform, and exchange rate policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet